Heard Island and the McDonald Islands: a window into the Kerguelen Plateau - Quilty, PG; Wheller, GE (Papers and Proceedings of the Royal Society of Tasmania, 2000)
The modern phase of volcanism on Heard Island probably is younger than one million years and is responsible for building Big Ben, the bulk of the island. The nearby McDonald Islands are less than 100 000 years old and are volcanically active. Big Ben sits on the Drygalski Formation, a Late Miocene-Early Pliocene volcanic/marine sediment with glacial influence, which occurs as a generally flat-lying, cliff forming unit over most of Heard Island. The "basement" of Palaeogene limestone crops out mainly on Laurens Peninsula but also sporadically beneath Big Ben and occurs as clasts in volcanics. Historical eruptions of Heard Island, most recently from 1985 to at least 1992 and probably later, have occurred from Mawson Peak, the summit cone built upon Big Ben, but young lavas and ash cones are widespread around the island. Recent volcanic activity is summarised. Heard Island and the McDonald Islands, with the Kerguelen Islands, are exposed parts of the Kerguelen Plateau, possibly the largest submarine plateau on earth, and provide geochemical and isotopic insights into the formation of oceanic plateaux, mantle plume development and the separation of Australia, India and Africa from Antarctica. The Plateau has a complex history that commenced with subaerial basaltic volcanism at 115 Ma, about 10 million years after India and Antarctica separated. It sank below sea level in the mid-Cretaceous, and subsided to its present setting as Broken Ridge and Kerguelen Plateau separated at 43 Ma when the Southeast Indian Ridge came between Australia and Antarctica. It is likely that, during its entire existence, some part of the plateau has been volcanically active, yielding a long-term geochemical record of large-scale crust-mantle evolution.